Misinterpretation of the Non-Literal Use of Body Idioms by Kurdish EFL Learners - Malik Yousif, Mukhalad; Abdalkarim Amin, Aras (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
Language may be used non-literally for multiple reasons and to achieve various purpose and this is a delicate nature which makes language so unique among other means of communications. The major concern of this paper is to thoroughly examine the improper interpretation of the non- literal use of body idioms particularizing the complications that Kurdish EFL learners may encounter while attempting at interpreting such idioms in certain given sentences. The paper focuses on revealing linguistic incompetence Kurdish EFL learners may encounter in this respect grouping such incompetencies according to the percentages of the improper occurrences in the interpretation of the body idioms, and, thus, demonstrating the significance of linguistic knowledge required for a better and an efficient language performance. To examine the possible inefficiency of the body idiom knowledge, a test compromising various body parts with non-literal sense in specific contexts is administered for the academic year 2023-2024. The results of the study reveal that Kurdish EFL learners lack knowledge concerning how body parts can be used nonliterally and this results into misinterpretation which can be grouped according to the influence of the linguistic factor resulting into such misinterpretation.